MALAKOK: Model Menegosiasikan Keragaman bagi Etnis Nias-Kristen dan Minangkabau-Islam di Kabupaten Padang Pariaman - Sefriyono Sefriyono (Turast: Jurnal Penelitian dan Pengabdian, 2015)
The awareness of the Nias-Christian as the comer in Minangkabau motivates them to do the malakok processionthrough the taking of the Minangkabau custom of Sungai Buluah society. That awareness was respondedby ninik mamak (the leadership of ethnic in Minangkabau) through the acceptance of their request. OnDecember 10, 1927 th was carried out the malakok procession by which the Nias-Christian paid the custompaying, 40 rial to the ninik mamak of Sungai Buluah village. The consequence of the malakok is the ninikmamak gave them the datuak title (the custom title in Minangkabau) and communal land in korong (part ofvillage) Tanjung Basung II. Even though, the role of datuak which was given to Nias-christian only managestheir nephew, they have become the dunsanak (family) of the Minangkabau society. In Minangkabau, fordunsanak is implemented the custom values, sasaki-sasanang, sahiduik-samati (if the dunsanak is sick, themember of it is also feel the sick, and if the dunsanak is happy, the member of it feel the happy as well). Thisagreement is always maintained and transmitted from generation to others by each of them (Nias-Christianand Minangkabau-Islam), so both of them are protected from the social conflict.